Classification in theory and practice - Batley, Sue (Chandos information professional series., 2014)
Following on from the first edition of this book, the second edition fills the gap between more complex theoretical texts and those books with a purely practical approach. The book looks at major library classification schemes in use in Europe, UK and the USA, and includes practical exercises to demonstrate their application. Importantly, classifying electronic resources is also discussed. Classification in Theory and Practice aims to demystify a very complex subject, and to provide a sound theoretical underpinning, together with practical advice and development of practical skills. Chapters concentrate purely on classification rather than cataloguing and indexing, ensuring a more in-depth coverage of the topic.--Provided by publisher.